The problem of communication among stakeholder in construction project - Noramirah, Abdul Rahaman (2015)
This research was conducted to identify the problem of communication failure in construction project from perspective of contractor and consultant. Besides that, the objective for this research to rank the most problem of communication failure in construction project in order to help contractor and consultant to be prepared with the solution because every contractor and consultant the unpredictable things. In this research, the method used for obtaining survey research was questionnaire for collecting the response from the contractor and consultant. The total respondents for this research were 32 from housing developer companies that categorized in G2 and located in Kuantan. Next, Statistical Package for the Social Science (SPSS) was used in analyzing these research findings. The result for this research showed that too much information was the most problem of communication failure in construction project with the highest mean. Last but not least, the main suggestion recommendation for future research is to study the large number of respondents or participants by include project team from different categories of contractors for more accurate outcome and represent a more realistic population in Malaysia.